Dynamics of the gut microbiome in subjects challenged with Shigella sonnei 53G in a controlled human infection model - Zachary Liechty; Arianna Baldwin; Sandra Isidean; Akamol Suvarnapunya; Robert Frenck; Chad Porter; Michael Goodson (mSphere)
ABSTRACT Shigella is a significant cause of diarrhea, predominantly affecting children in low- and middle-income countries, as well as international travelers. Not all individuals exposed to Shigella or other enteropathogens have symptomatic responses, and investigating the differences between symptomatic and asymptomatic individuals can further our understanding of enteropathogen proliferation and symptomatic responses. Here, we profiled the fecal microbiomes of 45 individuals infected with Shigella sonnei strain 53G through 16S rRNA sequencing in a controlled human infection model before and during infection, after antibiotic treatment, and after clinical recovery. This model allowed for a detailed exploration of microbiome temporal dynamics during infection, as well as a comparative analysis between those with shigellosis (defined as severe symptoms caused by Shigella infection, including severe diarrhea, fever, and/or abdominal pain) and those without shigellosis. Alpha diversity decreased to a greater degree in individuals with shigellosis. Perturbations in microbial composition during infection and antibiotic treatment were significantly larger in individuals diagnosed with shigellosis than in those who were not. Participants with shigellosis had persistent changes to their microbiomes after recovery, while those without shigellosis recovered to a composition resembling their pre-infection microbiomes. These persistent changes included taxa associated with gut inflammation, such as a decrease in Faecalibacterium and an increase in Ruminococcus gnavus. Furthermore, the initial microbiomes of participants who did not develop shigellosis had a greater abundance of taxa associated with short-chain fatty acid production than participants who did develop shigellosis, including Bifidobacterium, Roseburia, and Faecalibacterium. These data could help prevent Shigella infection or symptoms.IMPORTANCEDiarrheal disease is a major contributor to the global disease burden and can lead to an increased individual risk of chronic sequelae post-infection, such as irritable bowel syndrome, reactive arthritis, and altered gut permeability. Understanding the differential responses of individuals to enteropathogen exposure can elucidate factors that could lead to treatments or preventative measures to reduce the disease burden. Here, we use a controlled human infection model study to directly identify the effects of Shigella sonnei 53G infection on the microbiome. We identified taxa that were more or less abundant in participants who would develop shigellosis during the study, as well as persistent changes after recovery in the microbiomes of participants who developed severe symptoms. Understanding these changes could elucidate ways to prevent Shigella infection or recover altered microbiomes after recovery.CLINICAL TRIALSThis study is registered with ClinicalTrials.gov as NCT02816346.